The recording of one’s dreams in children, adolescents, and adults: the UK library study - Schredl, Michael (International journal of dream research, 2021)
Dream recording as a practice has been reported since the early days of empirical dream research. Online surveys have indicated that 17% to 24% of the participants have recorded their dreams at some point in their lives. The main factors associated with dream recording were dream recall frequency, gender, openness to experience, and low conscientiousness. The present study included 4849 participants (6 to 90 yrs. old) completing a dream questionnaire distributed via libraries throughout the UK. Overall, 14.77% of the sample reported that they had recorded dreams, with comparable figures in children, adolescents, and adults. The main factor associated with recording dreams was keeping a diary to record daytime events. Moreover, dream recall frequency, nightmare frequency, gender, and affinity to books (reading for fun, visiting the library) increased the likelihood of recording dreams. We were also able to replicate the finding that persons who record their dreams showed higher openness to experience and lower conscientiousness scores. It would be very interesting to study the motives for dream recording and its long-term effects, e.g., possible benefits regarding creative endeavors or coping with personal issues.
Gesehen am 19.04.2021